Top-down Tuning of Nanosized Zeolites by Bead-milling and Recrystallization - Wakihara, Toru; Tatami, Junichi (Journal of the Japan Petroleum Institute, 2013)
The fact that zeolites with high external surface area allow diffusing reactants greater access to active sites, has led to interest in the preparation of nanosized zeolites. The organic template-free synthesis of nanosized zeolite has been a subject of special importance for scientific and industrial applications. Thus far, most research has focused on a bottom-up approach for the fabrication of nano-zeolites, that is, control of zeolite nucleation and crystal growth during hydrothermal synthesis. This review summarizes a new method for the top-down production of nano-zeolite powder by first milling the zeolite to produce nanoparticles. This technique destroys the outer portion of the zeolite framework thereby decreasing its ion-exchange properties and catalytic activity. To remedy this, the damaged portions were recrystallized using a dilute aluminosilicate or silicate solution after bead-milling. The combined bead-milling and post-milling recrystallization yielded nano-zeolites with high crystallinity. The nanosized powders showed higher ion-exchange properties for zeolite A and higher catalytic activity for ZSM-5, respectively.